Hubungan Antara Ketersediaan Fasilitas Belajar Dengan Minat Belajar Peserta Pelatihan Menjahit Di Balai Latihan Kerja Kabupaten Kerinci - Afdila Santri Nurhalima; Vevi Sunarti (Universitas Negeri Padang, 2023)
The background of this research is the low interest in studying sewing training participants at the Kerinci Regency Vocational Training Center which is thought to be caused by the low availability of learning facilities. This study aims to describe the availability of learning facilities, describe the interest in learning and see the relationship between the availability of learning facilities and interest in learning. This research is a quantitative research with a correlational type. The population of this study were 40 sewing trainees. Sampling using stratified random sampling technique. Data collection techniques and tools using questionnaires and questionnaires. The data obtained were analyzed using percentage and correlation (product moment) formulas. The results showed that the availability of learning facilities was categorized as low, the learning interest of sewing training participants was categorized as low, and there was a significant relationship between the availability of learning facilities and the learning interest of sewing training participants at the Kerinci Regency Vocational Training Center.